2013
DOI: 10.5012/bkcs.2013.34.5.1435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Matrix on Electrochemical Performance of Si/C Composites for Use in Anodes of Lithium Secondary Batteries

Abstract: To investigate the influence of the carbon matrix on the electrochemical performance of Si/C composites, four types of Si/C composites were prepared using graphite, petroleum coke, pitch and sucrose as carbon precursors. A ball mill was used to prepare Si/C blends from graphite and petroleum coke, whereas a dispersion technique was used to fabricate Si/C composites where Si was embedded in disordered carbon matrix derived from pitch or sucrose. The Si/pitch-based carbon composite showed superior Si utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…5 One of these, enabling a better contact between silicon and carbon, is mechanical mixing or ballmilling of silicon particles with an organic carbon precursor, which is then converted into carbon by pyrolysis in inert atmosphere. Various carbon precursors were reported in the literature, some of them more common than others, such as polyvinyl chloride (PVC), [27][28][29][30][31] poly(vinyl alcohol) (PVA), 32,33 sucrose, 26,33 poly(p-phenylene) (PPP), 31 polyacrylonitrile (PAN), 34 polystyrene (PS), 35 pitch 26,[36][37][38][39][40][41][42] and other resins. [43][44][45] In some cases, carbon materials, such as graphite 27,28,34,37,41,44,45 or carbon nanotubes, 30 were added to the precursor mixture before the pyrolysis process to enhance carbon content.…”
mentioning
confidence: 99%
“…5 One of these, enabling a better contact between silicon and carbon, is mechanical mixing or ballmilling of silicon particles with an organic carbon precursor, which is then converted into carbon by pyrolysis in inert atmosphere. Various carbon precursors were reported in the literature, some of them more common than others, such as polyvinyl chloride (PVC), [27][28][29][30][31] poly(vinyl alcohol) (PVA), 32,33 sucrose, 26,33 poly(p-phenylene) (PPP), 31 polyacrylonitrile (PAN), 34 polystyrene (PS), 35 pitch 26,[36][37][38][39][40][41][42] and other resins. [43][44][45] In some cases, carbon materials, such as graphite 27,28,34,37,41,44,45 or carbon nanotubes, 30 were added to the precursor mixture before the pyrolysis process to enhance carbon content.…”
mentioning
confidence: 99%
“…Notably, c-Gr + 15% Si delivers a high capacity of 485.3 mA h g –1 after 400 cycles at 1 A g –1 , with only 0.02% average capacity loss per cycle (except the first two activation cycles); this performance is better than that reported for similar materials (Table S1). ,, According to Figure S6a, the capacity of the c-Gr + Si electrode is greater than that of the m-Gr + Si electrode because mixing Gr and Si directly leads to the agglomeration of active materials on the electrode. The capacity of m-Gr + Si is maintained at approximately 210–250 mA h g –1 , which is slightly higher than that of graphite (∼200 mA h g –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The optimized composition, c-Gr + 15% Si, where c-Gr denotes calcined and etched graphite, delivers a high capacity of 485.3 mA h g −1 after 400 cycles at 1 A g −1 , with a capacity retention of 92.9% (only 0.02% average capacity loss per cycle), which is better than the performance of Si/graphite composite electrodes developed in similar studies. [18][19][20]23,27 The results presented could offer a guide for the practical application of Si/graphite composites.…”
Section: ■ Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was also suggested that the carbon coating stabilizes the SEI and enhanced the electrode electronic conductivity. 22 Different carbon sources were tested as pitch, [23][24][25][26][27] acetylene, 28 citric acid, 29 pVdF, 30 glucose, 31 or dopamine, 32 with different deposition methods as PVD, pyrolysis, solgel, or hydrothermal. 33 Graphene layers have also been studied and showed encouraging results thanks to their high thermal and chemical stability, their high flexibility, and good electronic conductivity.…”
Section: Introductionmentioning
confidence: 99%